Conditional Sentencing - Hurtado Pozo, José (1973)
This article scrutinizes the institution of conditional sentencing within the Peruvian legal framework, examining its origins, evolution, and judicial implementation. It commences with an overview of the legislative backdrop surrounding conditional sentencing, addressing debates concerning its legal classification and nomenclature. The article further explores its overarching objective of mitigating the adverse repercussions of short prison terms, its statutory underpinnings, and the criteria for its application. Specific instances warranting conditional sentencing, such as cases involving sentences not exceeding six months, fines, or first-time convictions, are deliberated upon. Additionally, the article discusses scenarios indicating a favorable prognosis for the offender's future conduct and adherence to stipulated behavioral guidelines during a probationary period. Taking into account case-specific nuances, the author elucidates the implementation of conditional sentencing and examines comparative practices from foreign jurisdictions, such as probation, to provide context. In conclusion, the article advocates for comprehensive penal reforms to bolster the preventive efficacy of conditional sentencing and enhance the Peruvian penal system.